"This is for the Brown Kids!": Racialization and the Formation of "Muslim" Punk Rock. Issue 2 (April 2017) - McDowell, Amy D.
Recent research shows that non-Muslims "read" Muslim and non-Muslim Others through an Islamophobic lens, whether the victims of Islamophobia are practitioners of Islam or not. Yet how Muslims and non-Muslims band together against anti-Muslim racism in nonreligious ways and venues is less understood. The author draws on a wide range of qualitative data to show how "Taqwacore" punks ( taqwa means "God consciousness" in Arabic and core comes from hardcore punk ) create a racial identity as "brown kids" that is panethnic and opposed to the major racial frames used to vilify Muslims and brown-bodied Others. Taqwacore punks do this by (1) using punk rock attitudes to call out whiteness and keep it out of their punk and (2) redefining punk in favor of "brown kids." These findings expand a new body of scholarship that shows how marginalized youth are using popular culture to create new racial identities against whiteness.